1993
DOI: 10.1152/jappl.1993.74.6.2740
|View full text |Cite
|
Sign up to set email alerts
|

Muscle-fiber pennation angles are greater in hypertrophied than in normal muscles

Abstract: Muscle-fiber pennation angles were measured in vivo with the use of ultrasonography to investigate the relationship between fiber pennation and muscle size for 32 male subjects (from untrained subjects to highly trained bodybuilders). From the image of a B-mode ultrasonogram, fiber pennation angles and thickness of triceps brachii were determined, the former as angles between echoes from the interspaces of fascicles and from the aponeurosis of long and medial heads of triceps and the latter as the distance bet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

41
359
6
14

Year Published

2003
2003
2018
2018

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 438 publications
(420 citation statements)
references
References 11 publications
41
359
6
14
Order By: Relevance
“…Pennation, a key-parameter of muscle architecture, is a natural strategy to pack more contractile elements in to a given muscle volume. A decrease in pennation angle (θ), due to muscle atrophy, is commonly interpreted as a decrease in the number of fascicles in parallel (Kawakami et al, 1993). Reductions in θ seen after only short durations of ULLS or bed rest (~8-13% in the vastus lateralis muscle after 23 to 35 days, (de Boer et al 2007(de Boer et al & 2008 indicate that substantial muscle remodelling occurs with few days of muscle unloading.…”
Section: Introductionmentioning
confidence: 99%
“…Pennation, a key-parameter of muscle architecture, is a natural strategy to pack more contractile elements in to a given muscle volume. A decrease in pennation angle (θ), due to muscle atrophy, is commonly interpreted as a decrease in the number of fascicles in parallel (Kawakami et al, 1993). Reductions in θ seen after only short durations of ULLS or bed rest (~8-13% in the vastus lateralis muscle after 23 to 35 days, (de Boer et al 2007(de Boer et al & 2008 indicate that substantial muscle remodelling occurs with few days of muscle unloading.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, it was shown that the problem of electrode alignment can be overcome with principal component analysis (PCA), which was applied on multiple monopolar EMG channels and is thus unbiased with respect to the muscle fiber direction (Staudenmann et al, 2006). So far, PCA-processed monopolar multi-channel EMG has been applied on the triceps brachii, and triceps surae (Staudenmann et al, 2006(Staudenmann et al, , 2009a, both mainly pennate and architecturally complex muscles (Chow et al, 2000;Kawakami et al, 1993). A substantial improvement in muscle activation estimates was achieved with PCA as compared to multiple bipolar EMG using the same electrodes (Staudenmann et al, 2006(Staudenmann et al, , 2009a, suggesting that the misalignment of (multiple) bipolar EMG is a cause of errors in the estimation.…”
Section: Introductionmentioning
confidence: 99%
“…In healthy individuals, improved muscle function during strengthening exercise is due to improved neuromuscular adaptation (21), increased cross-sectional muscle fiber area (22,23), changes in fiber type composition (24), and metabolic changes (25)(26)(27). Healthy sedentary individuals usually respond to any type of exercise (28,29) and can attain a 40% increased muscle strength in 4 weeks, whereas longer periods of exercise are necessary to obtain the same effects in more trained individuals (23).…”
Section: Introductionmentioning
confidence: 99%